F-RecN + iRe-CoDeS: Computational framework for regional recovery simulation using advanced building recovery models - Blagojević, Nikola; Terzić, Vesna; Stojadinović, Božidar (Engineering structures, 2023)
•Advanced computational framework for evaluation of regional post-disaster recovery.•Integration of detailed building-level and region-level frameworks.•Data between two frameworks is exchanged through novel application programming interfaces.•New framework isolates damaged building components/systems and critical resources that dominate the recovery process of a region.•The framework is demonstrated on a virtual building stock located in a highly-seismic region. Disaster recovery models are essential for informed decision-making towards improving the disaster resilience of communities. Development of recovery models in the past decade took two, mostly independent, directions: one focused on building-level recovery modeling, and the other focused on modeling regional post-disaster recovery. This study aims to bridge the gap between the two post-disaster recovery modeling levels by providing a method for information exchange between the building-level and region-level recovery models. The implementation of such data exchange is done through application programming interfaces (APIs). First, API/I defines the information provided by building-level recovery models to the regional recovery model, labelled as PADDs: Preceding Activities, Demand and Duration for each recovery activity of all damaged buildings. Then, regional recovery model uses the PADDs to simulate the recovery of buildings while accounting for regional resource constraints, and then feeds back the recovery activity progress to the building-level recovery models through the API/O to generate building-level functional recovery curves. The result of this integration is a new post-disaster recovery framework, F-RecN + iRe-CoDeS, developed by integrating the building-level F-Rec recovery framework with the regional iRe-CoDeS recovery framework. The post-earthquake recovery of a set of buildings characteristic of the downtown Los Angeles region is used to illustrate the proposed integrated framework.